IMPLEMENTASI PEMBELAJARAN SENTRA PERSIAPAN DALAM MENINGKATKAN PERKEMBANGAN BAHASA ANAK USIA DINI DI KELOMPOK A2 TKIT 1 QURROTA A’YUN PONOROGO: IMPLEMENTASI PEMBELAJARAN SENTRA PERSIAPAN DALAM MENINGKATKAN PERKEMBANGAN BAHASA ANAK USIA DINI DI KELOMPOK A2 TKIT 1 QURROTA A’YUN PONOROGO - Siti Qomariah; Ratna Nila Puspitasari (UIN Kiai Ageng Muhammad Besari, 2023)
Language development is one aspect of a child's developmental stages that should not escape the attention of educators and parents. Therefore, this problem has received great attention from educators so that they can stimulate children's language development from an early age at TKIT 1 Qurrota A'yun Ponorogo. As in the observations made by researchers at TKIT 1 Qurrota A'yun Ponorogo using child-centred learning centers, this institution uses 4 centers, one of which is a preparation center. The preparation center stimulates children to dare to speak, express their opinions, express the feelings they are experiencing. This research aims to determine the development of preparatory learning centers in improving early childhood language development. This research uses qualitative research with a descriptive approach. The techniques used in collecting data are observation, interviews and documentation techniques. The results of this research are that after research was conducted at TKIT 1 Qurrota A'yun Ponorogo using preparatory learning centers, it was proven that early childhood language development was developing as expected. This can be seen from indicators of language development aged 4-5 years regarding understanding language, then indicators of language development aged 4-5 years regarding uncovering language, and then indicators of language development aged 4-5 years regarding literacy.